60 quick knits : 20 hats, 20 scarves, 20 mittens in Cascade 220 - Gray, Tanis; Sixth&Spring Books; Cascade Yarns (New York, N.Y. : Sixth&Spring Books, 2010)
Cascade 220 is 220 yards of 100% Peruvian highland wool in a classic worsted weight, and in this book, knitters can choose among dozens of projects, no matter what their skill level.
Keywords: Knitting -- Patterns; Hats; Scarves; Mittens